2010
DOI: 10.1002/pssa.201000785
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved Raman and cathodoluminescence probes in electronic materials: Basics and applications

Abstract: Spatially resolved spectroscopy of both Raman and cathodoluminescence (CL) emissions represent a quite powerful characterization method in electronics. In this paper, the underlying physics that dictates the different characteristics of Raman and CL probes is revisited, deepened, and further interpreted in order to clarify how the different nature of those probes enables one bringing about different sets of complementary information. Furthermore, it is inquired into the causes for which data collected by the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…6. The spectral convolutive algorithm can be set, as follows (Atkinson and Jain, 1999;Lipkin and Clarke, 1995;Pezzotti, 2011): where Δω l ðr ′ 0 ; z 0 Þ ¼ ω l ðr ′ 0 ; z 0 ÞÀω 0;l is the frequency shift observed for the l-th Raman band at each location of the geometrical center of the Raman probe with respected to the frequency recorded at an unperturbed location far away from the indentation crack, ω 0;l ðzÞ; I l;c ðzÞ and ω l;c ðzÞ are the deconvoluted profiles of Raman intensity and frequency shift along the thickness of the oxide scale for the l-th Raman band; and, the threedimensional response function for the Raman probe is given as:…”
Section: 3mentioning
confidence: 99%
“…6. The spectral convolutive algorithm can be set, as follows (Atkinson and Jain, 1999;Lipkin and Clarke, 1995;Pezzotti, 2011): where Δω l ðr ′ 0 ; z 0 Þ ¼ ω l ðr ′ 0 ; z 0 ÞÀω 0;l is the frequency shift observed for the l-th Raman band at each location of the geometrical center of the Raman probe with respected to the frequency recorded at an unperturbed location far away from the indentation crack, ω 0;l ðzÞ; I l;c ðzÞ and ω l;c ðzÞ are the deconvoluted profiles of Raman intensity and frequency shift along the thickness of the oxide scale for the l-th Raman band; and, the threedimensional response function for the Raman probe is given as:…”
Section: 3mentioning
confidence: 99%
“…These factors also affect graphene's phonon modes, and therefore, Raman spectroscopy is a useful method to reflect the variation of the properties [ 20 - 22 ]. In addition, Raman spectroscopy can be employed to determine strain, which modifies the characteristic of materials, such as band structure, and thus influences the performance of corresponding devices [ 23 - 25 ]. Recently, several groups study strain of graphene by artificially bending or stretching the film and then measuring the corresponding Raman spectra [ 26 - 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Raman spectroscopy becomes attractive to study domains orientation under external fields for in situ , nondestructive, and quantitative analysis . It was found that the intensity of some vibration modes, such as A 1 (TO) and A 1 (LO3), has a linear relationship with the polarization state of PZT.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Recently, Raman spectroscopy becomes attractive to study domains orientation under external fields for in situ, nondestructive, and quantitative analysis. 7,8 It was found that the intensity of some vibration modes, such as A 1 (TO) 9 and A 1 (LO3), 10 has a linear relationship with the polarization state of PZT. Besides, the relative intensity of some selected vibration modes, such as A1(TO) and B 1 , 11 E(2TO) and E (3TO + 2LO) + B 1 , 7 also relates to the polarization state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation